Subduing the nail barrier with novel herbal penetration enhancers for transungual delivery system - Singh, Vikram; Gupta, R. D.; Teotia, U. V. S (Journal of Applied Pharmaceutical Research, 2015)
Nail fungal infections are very common and also very difficult to treat because of nail morphology, deep penetrability of infectious agent inside nail plate and poor permeability of the nail plate. Transungual delivery shall be the first choice for treatment of nail infection if we get the effective penetration enhancers without causing the serious problem. In this study we tried to scanning some extracts penetration potency through the human cadaver nail plate. Five plants selected for the purpose acacia catechu, rosa hybrid, hibiscus rose-sinensis, tagetes patula, tagetes erecta. For penetration potency first defatted the nail plate with chloroform : methanol (2:1) mixture. Extracts of tagetes erecta, acacia catechu shows 100%, tagetes patula 60% and rosa hybrid 40% from dorsal side of plate. Those extracts were stable by it only. That proves that they may be used as a penetration enhancer to increase the penetration of drug